Study on the mechanism of coal pillar breaking and fracture development under repeated mining in a close seam group - Teng, Fei; Yu, Minggao; Han, Xuefeng; Chao, Jiangkun (Frontiers in Earth Science, 2023)
This study explored the influence of coal mining on an upper coal pillar under a repeated mining process of a close coal seam group, including the fracture and instability process and the influence mechanism of fracture development on the oxidation and spontaneous combustion of coal pillars. In this paper, FLAC3D numerical simulation software is used to simulate the dynamic evolution characteristics of stress, displacement and the distribution of the plastic area of the upper coal pillar in the Bulianta Mine, Shendong Mining Area. The results show that 1) the mining of the lower adjacent coal seam is a pressure relief process for the upper coal pillar under the condition of a staggered arrangement of the coal pillar in the lower adjacent coal seam. 2) The theoretical length of the fracture along the strike of the upper coal pillar is obtained by establishing the mechanical model of the upper coal pillar, which is consistent with the numerical simulation results. 3) In this paper, according to the dynamic evolution characteristics of displacement and stress on the coal pillar, the coal pillar is divided into the "step subsidence area", "fracture compaction area" and "reverse stress area", and the high spontaneous combustion risk area of the coal pillar is determined.